The impact of social networking site engagement on consumer’s knowledge of textile and apparel environmental sustainability: a Facebook experiment - Patwary, Sarif Ullah (Kansas State University, 2018)
The Textile and Apparel (TA) industry has become increasingly criticized for its massive environmental pollution through unsustainable production and distribution. In addition, key stakeholders are equally recognizing the need for cleaning up the industry. However, TA manufacturers, brands, and retailers need to be more aware of the necessity of sustainable production and distribution. At the same time, TA consumers need to be more aware of the necessity of sustainable consumption, care, and disposal of clothing. The purpose of this study was to investigate whether social networking sites (SNS) have any potential to increase consumer awareness of TA-related environmental sustainability issues. The specific research objectives were to investigate 1) whether engagement with TA-related environmental information in a SNS platform (i.e., Facebook) enhanced participants’ knowledge of TA environmental sustainability issues; 2) which format of TA-related environmental information sharing stimulated a higher level of SNS engagement and greater knowledge change; and 3) which content of TA-related environmental information sharing stimulated a higher level of SNS engagement and greater knowledge change. One group pretest-posttest experimental design was used, and mixed method approach was employed. Participants responded to a study-specific textile and apparel environmental sustainability knowledge (TAESK) scale before and after a Facebook experiment. The experiment included engaging with TA environmental information for a two-week period in a Facebook page. The researcher was the creator and administrator of the page. Quantitative data analysis included descriptive statistics, the Wilcoxon Signed-Ranks test, and multiple regression analysis. Qualitative analysis included conventional content analysis techniques. Findings from Wilcoxon Signed-Ranks test indicated that the experiment increased participants’ knowledge of TA environmental sustainability significantly (Z= -5.274, p< 0.001). Descriptive statistics revealed that video and infographic-type posts stimulated greater participants engagement than weblink (i.e., text based) posts. Likewise, participants were engaged with water and waste-related content of TA environmental sustainability more so than chemical and energy related content. However, the multiple regression analysis which was employed to identify the weighted influence of different formats and content of TA environmental sustainability information towards knowledge gain, provided limited information. This exploratory study provided some support for the usefulness of incorporating SNSs as part of an educational strategy by TA brands and policymakers advocating for sustainable TA production and distribution. Such a strategy may be one way to increase consumer awareness. Also, the findings of this study may motivate TA educators to weigh the potential of SNSs in teaching and learning activities related to TA sustainability issues.
Keywords: Knowledge; Environmental sustainability; Social networking sites; EngagementTextile and apparel